2020
DOI: 10.1111/nph.16887
|View full text |Cite
|
Sign up to set email alerts
|

Cellular requirements for PIN polar cargo clustering in Arabidopsis thaliana

Abstract: Cell and tissue polarization is fundamental for plant growth and morphogenesis. The polar, cellular localization of Arabidopsis PIN-FORMED (PIN) proteins is crucial for their function in directional auxin transport. The clustering of PIN polar cargoes within the plasma membrane has been proposed to be important for the maintenance of their polar distribution. However, the more detailed features of PIN clusters and the cellular requirements of cargo clustering remain unclear. Here, we characterized PIN clusters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 102 publications
3
30
0
Order By: Relevance
“…However, SA treatment markedly promoted the segmentation of PIN2-GFP with enhanced interval distances between clusters (Figs 3a, S2a,c). According to the definition in a previous study of the PIN2 clustering pattern (Kleine-Vehn et al, 2011) and recent findings (Li et al, 2020), we here found that SA-triggered hyperclustering of PIN2 predominantly exhibited as tiny (31%) and small islands (61%) (Figs 3a, S2c). Interestingly, REM1.2 exhibited a similar hyperclustering pattern after SA treatment (Fig.…”
Section: Sa Stimulates Pin2 Hyperclustering In a Rem12-dependent Mannersupporting
confidence: 80%
“…However, SA treatment markedly promoted the segmentation of PIN2-GFP with enhanced interval distances between clusters (Figs 3a, S2a,c). According to the definition in a previous study of the PIN2 clustering pattern (Kleine-Vehn et al, 2011) and recent findings (Li et al, 2020), we here found that SA-triggered hyperclustering of PIN2 predominantly exhibited as tiny (31%) and small islands (61%) (Figs 3a, S2c). Interestingly, REM1.2 exhibited a similar hyperclustering pattern after SA treatment (Fig.…”
Section: Sa Stimulates Pin2 Hyperclustering In a Rem12-dependent Mannersupporting
confidence: 80%
“…Microtubule organization and cell wall integrity might also participate in PIN clustering control; this relationship however remains to be elaborated in more detail [147]. This is also the case when it comes to elucidating PIN-PIP crosstalk in control of clustering.…”
Section: Plasma Membrane and Intrinsic Determinants In Pin Polarity Cmentioning
confidence: 99%
“…Furthermore, polar proteins show higher tendency of clustering when compared to non-polar plasma membrane proteins. Thus, variations in clustering could affect protein diffusion as a means to regulate their polar distribution [147]. However, how is such PIN clustering and intramembrane mobility controlled?…”
Section: Plasma Membrane and Intrinsic Determinants In Pin Polarity Cmentioning
confidence: 99%
See 2 more Smart Citations